2020
DOI: 10.1017/s1478951520000176
|View full text |Cite
|
Sign up to set email alerts
|

“I want to go home”: How location at death influences caregiver well-being in bereavement

Abstract: Objectives Goal concordant or congruent care involves having expressed wishes upheld. Yet, the preferred location for end-of-life care may be unaddressed. Caregiver–patient congruence between preferred and actual locations of care may influence the quality of life in bereavement. The study aimed to explore how the congruence between caregiver–patient preferred and actual locations of death influenced well-being in bereavement. Methods Mixed methods were employed. In-depth in-person inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…On the one hand, for these NHATS decease older adults, in-hospital death may reflect an acute, potentially unexpected decompensation with intensive medical interventions, potentially in conflict with preferences for end-of-life care in the home. 28 Indeed, among those NHATS participants who died in hospital, the LML survey asked the proxy respondent "where the respondent stayed just before the hospitalization" and the majority had been transferred there from home (78.2%), another hospital (10.6%) or nursing home (8.8%) before death. Our findings suggest that transitions between locations of care at end of life, which are already associated with worse perceptions of quality of end-of-life care, 29 are also associated with increased caregiver emotional strain.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, for these NHATS decease older adults, in-hospital death may reflect an acute, potentially unexpected decompensation with intensive medical interventions, potentially in conflict with preferences for end-of-life care in the home. 28 Indeed, among those NHATS participants who died in hospital, the LML survey asked the proxy respondent "where the respondent stayed just before the hospitalization" and the majority had been transferred there from home (78.2%), another hospital (10.6%) or nursing home (8.8%) before death. Our findings suggest that transitions between locations of care at end of life, which are already associated with worse perceptions of quality of end-of-life care, 29 are also associated with increased caregiver emotional strain.…”
Section: Discussionmentioning
confidence: 99%
“…A future study with a larger group of participants should continue to assess the effects on well-being outcomes and analyse whether this type of intervention is more suitable for certain subgroups of individuals with experience of informal caregiving. Previous research on former caregivers in general suggests that the post-caregiving experiences and outcomes may depend on, amongst other things, the characteristics of the past caregiving situation such as pre-loss levels of social support [ 8 , 9 ], pre-loss levels of depressive symptoms [ 7 , 9 ], and whether the care recipient died in the preferred setting [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the participants reported high scores on well-being is also in line with previous studies on post-caregiving health in general suggesting that for most former caregivers, adverse effects associated to intensive caregiving diminish with time [ 8 , 9 , 45 ]. Still, studies have also found that for some post-caregivers, negative health effects [ 7 , 8 , 9 , 44 , 45 ] such as insomnia, depressive symptoms, and feelings of guilt may prevail, even for as long as up to 10 years [ 7 ]. The specific needs of such vulnerable former caregivers should be further studied and met in interventions where they are the end-users.…”
Section: Discussionmentioning
confidence: 99%
“…There is little in the literature specific to end-of-life and Sense of Coherence. That contained in the literature presently concerns itself with caregivers of terminally ill people 27-29 . There is room for further research and development of Antonovsky's theory 30 .…”
Section: Existing Literaturementioning
confidence: 99%
“…That contained in the literature presently concerns itself with caregivers of terminally ill people. [27][28][29] There is room for further research and development of Antonovsky's theory. 30 Antonovsky had just begun contemplating the subject, which he presented in a speech at the University of California at Berkeley shortly before he died, but his ideas were in their genesis regarding end of life for older people.…”
Section: Existingmentioning
confidence: 99%